2016
DOI: 10.1002/adem.201600302
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Interface Investigation of Fe/Al2O3P Composite Activated by Ni and Ti

Abstract: Ceramic particles preforms are synthesized by vacuum sintering reaction between Al 2 O 3 particles and active elements Ti and Ni. The surface of preforms sintered by Al 2 O 3 and Ti consists of blockshaped a-Ti and fibrous TiO. As the content of Ti in preforms increases, the compressive strength of preforms rises first and then falls and the porosity decreases gradually. The preforms sintered of Al 2 O 3 and Ni-Ti have much higher compressive strength, because of the compact sintered shell outside Al 2 O 3 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Recently, AlNi 2 Ti was observed at the interface in zirconia-toughened alumina (ZTA) or Al 2 O 3 reinforced iron matrix composite with an Ni-Ti transition layer that is expected to be applied for wear-resistant material [33,34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, AlNi 2 Ti was observed at the interface in zirconia-toughened alumina (ZTA) or Al 2 O 3 reinforced iron matrix composite with an Ni-Ti transition layer that is expected to be applied for wear-resistant material [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…composite with an Ni-Ti transition layer that is expected to be applied for wear-resistant material [33,34]. The active elements Ni and Ti can promote the atom diffusion and chemical reaction between ZTA and Fe.…”
Section: Introductionmentioning
confidence: 99%
“…Ru et al [16] found electroless plated Ni and Cr on the surface of ZTA, and Ni and Cr diffused into the iron matrix under high temperature conditions, forming a diffusion interface layer, which improved the wettability of ZTA and matrix. In the existing literature, most of the Fe-ZTA cermets are prepared by molten metal die forging process [2,17,18], and the prepared Fe-ZTA cermet is often used to prepare wear-resistant materials, but the molding rate is low. The preparation of Fe-ZTA cermet material by powder metallurgy can effectively solve the problem of low molding rate of cermet and can achieve densification [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Over the recent decades, ceramic particulates reinforced metal matrix composites have attracted much attention owing to their superior wear resistance. In particular, Al 2 O 3 particulates (Al 2 O 3 p)-reinforced iron or steel matrix (Al 2 O 3 p/iron(steel)) composites have become the hot point of research and applications owing to their superior wear resistance and low costs [1][2][3][4][5][6]. However, the low ductility and toughness of Al 2 O 3 p/steel composites are the fatal weakness for their wider applications.…”
Section: Introductionmentioning
confidence: 99%